Yield of the electrophysiological study in patients with new-onset left bundle branch block after transcathether aortic valve replacement: The PR interval matters - Pagnoni, Mattia; Meier, David; Luca, Adrian; Fournier, Stephane; Aminfar, Farhang; Gentil, Pascale; Haddad, Christelle; Domenichini, Giulia; Le Bloa, Mathieu; Herrera-Siklody, Claudia; Cook, Stephane; Goy, Jean-Jacques; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Studies suggest that performing an electrophysiological study (EPS) may be useful to identify patients with new-onset left bundle branch block (LBBB) post-TAVR at risk of atrioventricular block. However, tools to optimize the yield of such strategy are needed. We therefore aimed to investigate whether 12-lead ECG changes post-TAVR may help identify patients with abnormal EPS findings. Materials and methods Consecutive patients with new-onset LBBB post-TAVR who underwent EPS were included. PR and QRS intervals were measured on 12-lead ECG pre-TAVR and during EPS. Abnormal EPS was defined as an HV interval > 55 ms. Results Among 61 patients, 28 (46%) had an HV interval > 55 ms after TAVR. Post-TAVR PR interval and ΔPR (PR-post–pre-TAVR) were significantly longer in patients with prolonged HV (PR: 188 ± 38 vs. 228 ± 34 ms, p < 0.001, ΔPR: 10 ± 30 vs. 34 ± 23 ms, p = 0.001), while no difference was found in QRS duration. PR and ΔPR intervals both effectively discriminated patients with HV > 55 ms (AUC = 0.804 and 0.769, respectively; p < 0.001). A PR > 200 ms identified patients with abnormal EPS results with a sensitivity of 89% and a negative predictive value (NPV) of 88%. ΔPR ≥ 20 ms alone provided a somewhat lower sensitivity (64%) but combining both criteria (i.e., PR > 200 ms or ΔPR ≥ 20 ms) identified almost every patients with abnormal HV (sensitivity = 96%, NPV = 95%). Selecting EPS candidate based on both criteria would avoid 1/3 of exams. Conclusion PR interval assessment may be useful to select patients with new-onset LBBB after TAVR who may benefit most from an EPS. In patients with PR ≤ 200 ms and ΔPR < 20 ms the likelihood of abnormal EPS is very low independently of QRS changes.